2018
DOI: 10.1089/jpm.2017.0418
|View full text |Cite
|
Sign up to set email alerts
|

Early Palliative Care and Its Impact on End-of-Life Care for Cancer Patients in Brazil

Abstract: Among cancer patients in Brazil, late referral to palliative care is common. Patients who enter palliative care earlier appear to receive less aggressive end-of-life treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 34 publications
1
17
0
4
Order By: Relevance
“…In our study, we found that patients who received palliative care and their FCs have more needs than those who did not receive palliative care. Although, it can be expected that those who received palliative care are more ill (tended to be inpatients and lower KPS) and therefore have more needs, as early palliative care has been proven to improve the QOL of the patients with advanced cancer [52][53][54][55][56], we postulate that this may also imply that patients with advanced cancer were referred by their oncologists to palliative care physicians late in their cancer trajectory. This late referral may have resulted in patients who are more ill and therefore, have more needs and require more care.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In our study, we found that patients who received palliative care and their FCs have more needs than those who did not receive palliative care. Although, it can be expected that those who received palliative care are more ill (tended to be inpatients and lower KPS) and therefore have more needs, as early palliative care has been proven to improve the QOL of the patients with advanced cancer [52][53][54][55][56], we postulate that this may also imply that patients with advanced cancer were referred by their oncologists to palliative care physicians late in their cancer trajectory. This late referral may have resulted in patients who are more ill and therefore, have more needs and require more care.…”
Section: Discussionmentioning
confidence: 94%
“…The findings that almost 75% of the patients group and almost 63% of the FCs group cared for patients who were not referred to palliative care physicians in spite of their advanced stage in cancer, and patients have also identified under the domain on “Information” as the top second information needs as “I needed information about palliative care services” may add credence to this view. In order to ascertain the real reason why patients and their FCs who received palliative care have more needs, further study would be needed as late referral to palliative care is associated with aggressive end of life treatment [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In them, PC consultation was described as late in 60.5% of the patients; a higher rate of late PC consultation has been reported in a cohort of cancer patients in Tennessee, USA (84.5%) [ 16 ]. In Brazil, cancer patients have been referred to palliative care late in the course of the disease [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different figures have been reported from different studies carried out in various countries. In Brazil [ 17 ], the mean time from entry into PC service to death was 72 days. In the USA [ 18 ], the median times were 42 and 57 days in two different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Only a minority of doctors in our study understood palliative care by the newer de nition. Oncology research in various countries suggests physicians' understanding of palliative care as equivalent to end-of-life care can be a barrier to early use of palliative care for advanced cancer patients [9,29,30]. Because many patients in China already have advanced cancer at the time of diagnosis, there is particular need for palliative care early in treatment to aid quality of life [2].…”
Section: Discussionmentioning
confidence: 99%